The Heterogeneity of the Internal Transcribed Spacers (ITS) of rDNAs in Imperata cylindrica in Taiwan - Chi-Chu Tsai (Taiwania, 2000)
Ribosomal DNA for internal transcribed spacers ITS, ITS1, 5.8S rRNA gene, ITS2 and the adjoining regions of the 17S and 25S rRNA genes were obtained from 45 individuals of Imperata cylindrica (Cogongrass) in Taiwan via PCR amplification. The length of each PCR product was 692 bp, except for one sample (about 702 bp). All ITS DNA fragments were digested with EcoRV, CfoI, BanI, HaeIII, MspI, HinfI, BstOI, Sau96I, StyI and Eco109I, respectively. The ITS, including ITS1, 5.8S rRNA gene and ITS2, were very heterogeneous within an individual of Cogongrass in Taiwan. Of 45 individuals of Cogongrass in Taiwan, the ITS1 and ITS2 regions showed at least eight type variants, and 5.8S rRNA gene showed at least five type variants among Cogongrass population in Taiwan based on PCR-amplified RFLP. In conclusion, the ITS repeat sequences from Cogongrass in Taiwan was very high heterogeneous.